Research progress in gene editing technology - Sheng Huang; Yali Yan; Fei Su; Xiaorui Huang; Dandan Xia; Xinxin Jiang; Yinghui Dong; Ping Lv; Fangyuan Chen; Yanwei Lv (Frontiers in Bioscience-Landmark, 2021)
As a tool for modifying the genome, gene editing technology has developed rapidly in recent years, especially in the past two years. With the emergence of new gene editing technologies, such as transposon editing tools, numerous advancements have been made including precise editing of the genome, double base editing, and pilot editing. This report focuses on the development of gene editing tools in recent years, elaborates the progress made in classic editing tools, base editor and other new editing tools, and provides insights into challenges and opportunities.